2004
DOI: 10.1037/0893-164x.18.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking Among Latino Youth: Role of Acculturation-Related Variables.

Abstract: This research examined the relationship between acculturation-related variables and binge drinking behavior among nationally representative samples of Mexican American, Cuban American, and Puerto Rican youth. It explored the relationship between length of residence in the United States, type of language spoken in the home (Spanish vs. English) and binge drinking in each of these subgroups. Results suggest that Latino youths with no prior history of alcohol consumption remain largely unaffected by these accultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 29 publications
2
50
1
Order By: Relevance
“…This finding is not necessarily inconsistent with the existing literature because most of the studies examining the linkage do not include monolingual Spanish speakers (i.e., Balcazar et al, 1996;Brooks et al, 1998;Carvajal et al, 1997;Epstein et al, 1996;Felix-Ortiz & Newcomb, 1995;Gil et al, 2000;Guilamo-Ramos et al, 2004;Marsiglia et al, 2004;Perez et al, 1980). Hence, it is difficult to know from the existing literature whether it is just enculturation, as represented by the use of Spanish language, or biculturalism that is truly protective.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This finding is not necessarily inconsistent with the existing literature because most of the studies examining the linkage do not include monolingual Spanish speakers (i.e., Balcazar et al, 1996;Brooks et al, 1998;Carvajal et al, 1997;Epstein et al, 1996;Felix-Ortiz & Newcomb, 1995;Gil et al, 2000;Guilamo-Ramos et al, 2004;Marsiglia et al, 2004;Perez et al, 1980). Hence, it is difficult to know from the existing literature whether it is just enculturation, as represented by the use of Spanish language, or biculturalism that is truly protective.…”
Section: Discussionmentioning
confidence: 90%
“…Still others have found that the relation between acculturative status and substance use is more complex than previously understood (Guilamo-Ramos, Jaccard, Johansson, & Turrisi, 2004;Marsiglia et al, 2004). Latino adolescents from Spanish speaking homes reported heavier episodic drinking than Latino adolescents from English speaking homes (Guilamo-Ramos et al, 2004). However, this difference disappeared with greater levels of exposure to the U.S.…”
Section: The Role Of Enculturation and Acculturation In Substance Usementioning
confidence: 96%
See 1 more Smart Citation
“…Other study exhibit that first generation South Asians and linguistically acculturated Vietnamese were at an increased risk of binge drinking (Becerra et al 2013). However, Latino young immigrants with no prior history of alcohol consumption remained largely unaffected by these acculturation-related variables, but young immigrants with a previous history of alcohol consumption experienced greater likelihood of binge drinking as a function of the acculturation-related variables (Guilamo-Ramos et al 2004). …”
Section: Language Sub-groupsmentioning
confidence: 99%
“…Social influences such as the pro-smoking, pro-alcohol use related social norms of the United States and the social acceptability of health risk behaviors in United States society also have been found to influence alcohol use behaviors among adolescent immigrants (Guilamo-Ramos, Jaccard, Johansson, & Tunisi, 2004), including international students (Unger et al, 2000).…”
Section: The Relation Of Acculturation Processes To Alcohol Use Patternsmentioning
confidence: 99%